Structural proteins of West Nile virus are a major determinant of infectious particle production and fitness in astrocytes - Hussmann, Katherine L. (Society for General Microbiology, 2014)
The molecular basis for the increased resistance of astrocytes to a non-neuropathogenic strain of West Nile virus (WNV), WNV-MAD78, compared with the neuropathogenic strain WNV-NY remains unclear. Here, we demonstrated that the reduced susceptibility of astrocytes to WNV-MAD78 is due to a combination of both cellular activities as well as viral determinants. Analyses of the viral particle indicated that astrocyte-derived WNV-MAD78 particles were less infectious than those of WNV-NY. Additionally, inhibition of cellular furin-like proteases increased WNV-MAD78 infectious particle production in astrocytes, suggesting that high levels of furin-like protease activity within these cells acted in a cell- and strain-specific manner to inhibit WNV-MAD78 replication. Moreover, analysis of recombinant viruses indicated that the structural proteins of WNV-MAD78 were responsible for decreased particle infectivity and the corresponding reduction in infectious particle production compared with WNV-NY. Thus, the composition of the WNV virion was also a major determinant for viral fitness within astrocytes and may contribute to WNV propagation within the central nervous system. Whether the WNV-MAD78 structural genes reduce virus replication and particle infectivity through the same mechanism as the cellular furin-like protease activity or whether these two determinants function through distinct pathways remains to be determined.